Maslahah-Based Judicial Reasoning in Isbat Nikah Cases: Reconciling Legal Certainty and Substantive Justice in the Makassar Religious Court - Fajriyati, Siti Nur; Asni; Ilyas, Musyfikah (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2026)
The tension between statutory marriage registration requirements and the socio-religious legitimacy of nikah siri (unregistered marriages) continues to create challenges in the implementation of family law in Indonesia. This article critically examines the judicial reasoning employed by judges of the Makassar Class IA Religious Court in adjudicating isbat nikah (judicial validation of unregistered marriage) cases from the perspective of maslahah. This study employs normative juridical research using case-based and conceptual approaches, with judicial decisions and statutory regulations analyzed as primary legal materials. The findings reveal that the adjudication of isbat nikah cases extends beyond procedural-administrative considerations through responsive judicial reasoning grounded in maslahah. Judges utilize isbat nikah mechanisms to protect children’s legal identity and civil rights through the principle of hifz al-nasl (protection of lineage), while also reconciling tensions between state legal formalism and socially embedded Islamic marital practices. In certain cases, applications are rejected to prevent procedural abuse and legal circumvention based on the principle of dar’ al-mafasid (prevention of harm). This study demonstrates that maslahah functions as a foundational framework of judicial reasoning aimed at realizing legal certainty and substantive justice within plural legal systems.